EPISTEMOLOGI KRITIK HADIS - Hedhri Nadhiran (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2017)
Hadith is agreed as the second source of Islamic teachings after the Qur'an. However, in order to make it the basis of doctrine, hadith must pass the test of naqd al-hadis and fiqh al-hadis. Related to naqd al-hadis, the problem that arises is how to make a hadith can be believed or allegedly derived from the Prophet, since the hadith is historical data about past events, in this case the life of the Prophet. What is a measuring tool (method) that can be used to test a hadith until it is believed authenticity comes from the Messenger of Allah. This question arises from the history of the hadith journey narrated by many narrators with diverse characters, the hadith is also 'vulnerable' to fraud and deviation, and its messenger process tends to be ahad, thus making the problem of authenticity of hadith become a very widespread discourse - even since Rasulullah saw, died. To that end, the scholars then formulated a theory that was agreed as a